Modelling policies to improve affordability and consumptionof nutritious foods for complementary feeding in Kenya - Traoré, Fousseini; Omolo, Miriam; Beal, Ty; Nordhagen, Stella; Codjia, Patrick; Kiige, Laura; Kamudoni, Penjani; Arimi, Caroline; Kirogo, Veronica (Wiley, 2024)
In Kenya 26% of children under age 5 experience stunted growth, 4% are wasted and 11% are underweight. In pregnant women, the prevalence of iron deficiency is 36% and iron-deficiency anaemia prevalence is 26%. Previous studies have identified affordability as a key barrier to the intake of nutrients, particularly from animal-source foods (ASFs). Thus, this study analyzes to what extent the affordability of ASF in Kenya can be improved. It focuses on four ASFs: eggs, milk, chicken and beef. Using a computable general equilibrium model, three policy simulations were undertaken to establish the impact of potential changes on nutritious ASF availability and affordability: a 20% increase in total factor productivity (TFP) for the four products; a 20% TFP increase plus a 25% reduction in trade and transportation margins; and a 20% TFP increase for ASF and maize (a key input in animal feed). Simulations suggest increasing the productivity of the four ASF products would increase their availability and lower consumer prices (up to 17% lower). Household consumption of the four commodities would increase, resulting in improved household dietary diversity. Rural households would gain more compared with urban households. Poor households (the lowest 40%) would register larger welfare (Equivalent Variation) gains than other households in both urban and rural areas. The richest 20% of the population would neither lose nor gain following the policy changes. Reducing transportation costs and trade margins and increasing maize productivity could further reduce the price of ASFs through lower production costs and increased consumption.